PENGARUH PRICE BOOK VALUE (PBV), EARNING PER SHARE (EPS), DAN VOLUME PERDAGANGAN TERHADAP HARGA SAHAM (Studi Pada Perusahaan LQ 45 di Bursa Efek Indonesia) - Nisa Arini; Noor Shodiq Askandar; Anik Malikah (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine the effect of the corporate fundamental variables and trading volume on stock prices. The population of this study is companies included in the LQ45 index listed on the Indonesia Stock Exchange (IDX). The sample selection was using a purposive sampling method. Based on these criteria that obtained 45 populations and 30 samples of the company. The method used in this study is multiple linear regression analysis, and testing classic assumptions using multicollinearity test, heteroscedasticity test, autocorrelation test, and hypothesis testing using the coefficient of determination test, F test and t test. The results of this study are Price Book Value (PBV), Earning Per Share (EPS), Trading Volume and a positive and significant effect on Stock Prices.Keyword : Price Book Value (PBV, Earning Per Share (EPS), Trading Volume Activity and Stock Price.